2003
DOI: 10.1093/geront/43.6.875
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Assisted Living Facilities

Abstract: ALFs differed widely in ownership, size, policies, and the degree to which they manifested the philosophy of assisted living. This diversity represents a challenge for consumers in terms of selecting an appropriate facility and for policy makers in terms of deciding what role they want assisted living to play in long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(167 citation statements)
references
References 0 publications
2
161
4
Order By: Relevance
“…However, according to a past study in Shanghai, private rooms only accounted for 9.25% of the bedrooms in current facilities 3) . In contrast, in a national survey of assisted living facilities in America, 73% of the bedrooms were private ones 4) .…”
mentioning
confidence: 89%
“…However, according to a past study in Shanghai, private rooms only accounted for 9.25% of the bedrooms in current facilities 3) . In contrast, in a national survey of assisted living facilities in America, 73% of the bedrooms were private ones 4) .…”
mentioning
confidence: 89%
“…The numbers of RCFs and RCF residents are growing rapidly. In the United States, there are approximately 45,000 RCFs serving nearly a million people (Consumer Reports, 2005;Hawes, Phillips, Rose, Holan, & Sherman, 2003;NCAL, 2010). In addition, the RCF "market" is changing in response to changes elsewhere in the health care system.…”
Section: Many In the United States Believe Elder Mistreatment In Longmentioning
confidence: 99%
“…States view assisted living as a costeffective means of providing long-term care, because Medicaid covers only services in assisted living but covers rent, food, and services in nursing homes (Carder, Wright, & Jenkens, 2006) and the majority of assisted living residents are private pay and not dependent on the public financing system (Hedrick et al, 2003). Assisted living became the fastest growing type of senior housing by the late 1990s (Hawes, Phillips, Rose, Holan, & Sherman, 2003).…”
Section: Community Residential Carementioning
confidence: 99%
“…For example, in a national survey of assisted living administrators, Hawes and colleagues (2003) found that although residents of assisted living have more privacy and control than residents of nursing homes, a significant portion of facilities do not adhere to the principles of assisted living. In addition, although early proponents of assisted living viewed it as a way to prevent nursing home admission for those who seemed destined for such an institution (Wilson, 2007), this same survey reported that a substantial percentage of facilities refuse to admit or retain those who need nursing home services (Hawes et al, 2003).…”
Section: Community Residential Carementioning
confidence: 99%